THOUGHT OF NUSANTARA MOSLEM SCHOLARS: FIQH CONCEPTS OF SYEIKHARSYAD AL-BANJARI IN SABILALMUHTADIN - Muhammad Roy Purwanto (Akademika : Jurnal Pemikiran Islam, 2019)
In the current context, the fiqh concepts of ulama nusantara(Nusantara Moslem Scholars) are important to be discussed as it has local wisdoms, progressivity, and adaptability in giving solutions to the society’s problems. This paper will discuss the fiqh concepts ofSyeikhArsyad al-Banjari in his book entitled SabilalMuhtadin that discusses fiqh(Islamic jurisprudence) in the perspective of Nusantara’s society, especially Banjarese society. This paper uses normative-sociological approach in analyzing the fiqh concepts of SyeikhArsyad al-Banjari, such as, zakat receivers, floating lavatory, corpse burial in coffin (tabala), and providing food for mourners. The results of the study indicate that al-Banjariwas mainly relied on “custom is law” (al-adatumuhakkamah) and “generating benefits or mashlahah and declining damage” (jalb al-mashalihwadar’ al-mafasid) in his ijtihad (independent reasoning). He also believed that law evolved according to the society’s situation and condition (taghayyur al-ahkamyata’allaqu bi taghayyur al-azminahwa al-amkinah). All of al-Banjari’s concepts are in-line with Syafi’iyyah school. Keywords: Ijtihad, Fiqh, Nusantara, and Sabilal Muhtadin